2014
DOI: 10.1107/s1399004714002260
|View full text |Cite
|
Sign up to set email alerts
|

Accurate macromolecular crystallographic refinement: incorporation of the linear scaling, semiempirical quantum-mechanics programDivConinto thePHENIXrefinement package

Abstract: Macromolecular crystallographic refinement relies on sometimes dubious stereochemical restraints and rudimentary energy functionals to ensure the correct geometry of the model of the macromolecule and any covalently bound ligand(s). The ligand stereochemical restraint file (CIF) requires a priori understanding of the ligand geometry within the active site, and creation of the CIF is often an error-prone process owing to the great variety of potential ligand chemistry and structure. Stereochemical restraints ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 63 publications
4
81
0
Order By: Relevance
“…[142,143] In 2004, ar elated approach was presented, in which a linear-scaling semiempiricalQ Mm ethod was employedf or the entire protein, obtained by simplyr eplacing E MM in Equation (7) by E QM . [52,138,144] Chem. This approach has later been extended to other software, including also QM/MM and ab initio methods.…”
Section: Wavefunction-based Refinementmentioning
confidence: 99%
“…[142,143] In 2004, ar elated approach was presented, in which a linear-scaling semiempiricalQ Mm ethod was employedf or the entire protein, obtained by simplyr eplacing E MM in Equation (7) by E QM . [52,138,144] Chem. This approach has later been extended to other software, including also QM/MM and ab initio methods.…”
Section: Wavefunction-based Refinementmentioning
confidence: 99%
“…While PDB_Redo (Cereto- Massagué et al, 2013) has shown that improvements to the quality of the model can be made, we have shown that there is a limit, when using restraint dictionaries, to how much of an improvement can be made to ligand conformation energy and geometry. As a move is made to obtain more accurate models, it is our hope that refinement target functions will more often be implemented according to the paradigm presented here (Borbulevych, Plumley et al, 2014;Smart et al, 2010Smart et al, , 2014) so as to more accurately represent the complex conformational space of small-molecule ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The latter approaches are often complicated to use, requiring multiple additional steps from the user. They are therefore difficult to integrate into an automated workflow and the speed requirements of many modern-day high-throughput laboratories such as those involved in pharmaceutical drug discovery (Borbulevych et al, 2016;Borbulevych, Plumley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies using quantum calculations to evaluate ligand strain provide more evidence that this problem is pervasive. 4,6 ■ COMMON ISSUES How can so many bound-ligand structures have problems? There are many reasons.…”
Section: ■ Evidence Of a Problemmentioning
confidence: 99%